Transformasi Kebijakan Bantuan Sosial Menuju Peningkatan Kesejahteraan Masyarakat Miskin melalui Integrasi Perspektif Maqasid al-Syariah - Faiqoh, Fadhila; Prasetyowati, Riris Aishah; Sujoko, Imam (Prediksi : Jurnal Administrasi dan Kebijakan, 2026)
The Non-Cash Food Assistance (BPNT) and Prosperous Rice (Rastra) programs are designed as policy instruments to improve the welfare of the poor, but their effectiveness requires an in-depth evaluation from the perspective of sharia maqashid. Through a quantitative approach involving 100 respondents using a systematic random sampling technique in Tanjung Harapan Village, Kotabumi, North Lampung, this study reveals the dynamics of the aid distribution mechanism and its impact on community welfare. Data was collected through interviews and questionnaires, then analyzed using SmartPLS to evaluate measurement and structural models. The findings identified serious problems in the form of uneven distribution, inaccuracy of recipient targets, and administrative weaknesses that hinder the effectiveness of the program. However, the integration of the perspective of sharia maqashid showed a very significant positive influence with a path coefficient of 0.817 between political policy and sharia maqashid, and 0.822 between sharia maqashid and welfare. The implementation of BPNT and Rastra has been proven to contribute to the protection of life, heredity, intellect, and religious aspects, although the aspect of asset protection still needs improvement. The findings confirm that social assistance policies that are in line with the principles of sharia maqashid have a strong and sustainable impact, so comprehensive improvements are needed to the data collection system, transparency of distribution, and integration with economic empowerment programs.